2007
DOI: 10.1075/eurosla.7.09gob
|View full text |Cite
|
Sign up to set email alerts
|

Success and failure in the EFL classroom

Abstract: This paper describes a study into learners’ attributions for success and failure in learning English as a foreign language. The study investigated perceived reasons for successes and failures on actual language learning tasks in both oral communication and reading classes, looking at how learners judge their successes and failures, and their range of attributions. A questionnaire was created based on attribution theory focusing on the attributions of ability, effort, task difficulty, and luck and was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Ushioda (2001) found that respondents who were university French learners attributed success to internal locus while attributions for failure were external. In contrast, Gobel and Mori (2007) www.ccsenet.org/ass Asian Social Science Vol. 9, No.…”
Section: Attribution Theory and Language Learningmentioning
confidence: 95%
“…Ushioda (2001) found that respondents who were university French learners attributed success to internal locus while attributions for failure were external. In contrast, Gobel and Mori (2007) www.ccsenet.org/ass Asian Social Science Vol. 9, No.…”
Section: Attribution Theory and Language Learningmentioning
confidence: 95%
“…However, most of these studies do not provide enough information on the validation of the questionnaire and seem to follow procedures for the creation of the instrument and the analysis of the results that do not abide by standard rules in questionnaire methodology (Ishikawa, Negi & Tajima, 2011;Gobel & Mori, 2007;Pishghadam & Modarresi, 2008;Pishghadam & Zabihi, 2011;Wu, 2011).…”
Section: Attribution Theory: Exploring the Reasons For Success And Famentioning
confidence: 99%
“…Still, within the field of educational motivation, and most precisely in the context of foreign language (L2) learning, attribution theory (AT) has not received sufficient attention. A few studies have explored the attributions to success and failure of foreign language students from a qualitative approach (e.g., Gabillon, 2013;Gonzalez, 2011;Williams & Burden, 1997Williams, Burden, & Al-Baharna, 2001;Williams, Burden, & Lanvers, 2002;Williams, Burden, Poulet, & Maun, 2004;Yan & Li, 2008), while a few others have attempted to measure these attributions quantitatively by using questionnaires that were not always properly designed, piloted and statistically validated to be fit for the study (Gobel & Mori, 2007;Ishikawa, Negi, & Tajima, 2011;Pishghadam & Modarresi, 2008;Pishghadam & Zabihi, 2011;Wu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that those who attributed success to internal factors, such as ability or effort, demonstrated more self-regulated language learning behaviors. Gobel and Mori (2007) conducted a research with the aim of constructing a questionnaire of attributions and also examining the relationship between EFL language learning and attributional beliefs among two hundred and thirty-three EFL students in Japan. The results of their study highlighted significant relationships between ability, task difficulty, and exam scores in oral communication and reading classes.…”
Section: Perceived Attributions In Second and Foreign Language Conmentioning
confidence: 99%